Separation of sources and 3D inversion of gravity and magnetic data for the Thuringian Basin, Germany - Ilya PRUTKIN (Contributions to Geophysics and Geodesy, 2012)
We propose a novel methodology for separation of potential field sources and its 3D inversion. New approaches are developed to separate sources: i) in depth using a succession of upward and downward continuation; ii) in the lateral direction by means of approximation with the field of 3D line segments; iii) according to density and magnetization contrast based on pseudo-gravity calculation. Our original inversion algorithms allow the recovery of unknown 3D geometry both for a restricted body of arbitrary shape and for a contact surface. For the first time, we apply our algorithms to joint inversion of gravity and magnetic data for a large area (the Thuringian Basin in central Germany). We separate in depth sources of both gravitational and magnetic anomalies for the whole territory of Thuringia and compare corresponding components. A 3D model of the main sources is presented based on approximation with 3D line segments and their further transforming into a restricted body or a contact surface with the same field.